Mediating effect of psychological distress and mindful eating behaviors between orthorexia nervosa and academic self-efficacy among Lebanese university female students - Muna Barakat; Nesreen A Salim; Diana Malaeb; Mariam Dabbous; Fouad Sakr; Souheil Hallit; Feten Fekih-Romdhame; Sahar Obeid (BMC, 2024)
Abstract Objectives This study examined the mediating effect of psychological distress and mindful eating behaviors between orthorexia nervosa and academic self-efficacy among Lebanese university female students. Methods A total of 769 female participants enrolled in this cross-sectional study (mean age 21.58 ± 3.20 years). A self-administered questionnaire was distributed among university female students. The questionnaire consisted of Mindful Eating Behaviors Scale, ORTO-R, Depression Anxiety Stress Scale, and Arabic version of Academic Self-Efficacy Scale. Results The results showed that psychological distress fully mediated the association between orthorexia nervosa and academic self-efficacy; higher orthorexia nervosa was significantly associated with less psychological distress (β= -0.31, p =.05), with more psychological distress significantly associated with lower academic self-efficacy (β= -0.32, p =.09). Focused eating fully mediated the association between orthorexia nervosa and academic self-efficacy; higher orthorexia nervosa was significantly associated with less focused eating (β=-0.09, p =.04), with more focused eating significantly associated with better academic self-efficacy (β = 1.40, p =.10). Orthorexia nervosa was not directly associated with academic self-efficacy in both models. Conclusion This study shed light on important connections between orthorexia nervosa, psychological distress, mindful eating behaviors, and academic self-efficacy within the Lebanese context. The findings will have practical implications for both educational institutions and healthcare providers striving to support young female adults' overall well-being and academic success.